Pengaruh Volatilitas Penjualan, Volatilitas Arus Kas dan Tingkat Utang Terhadap Persistensi Laba - Wendy Salim Saputra; Phebyana Margaretha (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
Profit is a very important role as an indicator of the company's performance evaluation. Profit information will be useless if it is not of good quality, the more a company can produce quality profit information, the more it will reflect the sustainability, financial condition, and performance of the company in the future. Quality earnings are profits that contain a predictive value, which is one aspect of relevance in fundamental quality, which is the ability of accounting information to be used as a basis for predicting future figures. The level of persistence of earnings can describe the effect of the current year's earnings on future profits, the basis of the calculation is core earnings so that the profits presented in the report are profits that are relevant to the company's routine operational processes and are not the result of transitory items or extraordinary income items. Earnings persistence can also describe how much income the company can maintain to get in each operational period. The higher persistence of earnings, the better the company is at maintaining its income level. The purpose of this study was to obtain empirical evidence regarding the effect of sales volatility, cash flow volatility, and debt levels on earnings persistence. This research will then use multiple regression analysis which begins with descriptive statistical testing, classical assumption testing, and hypothesis testing. Data testing is assisted by using the SPSS program. The results of the T-test showed that the earnings persistence was not affected by the sales volatility variable in a negative direction, the cash flow volatility variable had a positive but not significant effect on earnings persistence, and the level of debt had a positive but not significant effect on earnings persistence.